Impact of Early and Delayed Stoma Closure on Patients and Their Family Life: Early vs Delayed Stoma Closure Outcomes - Karim, Tahira; Kumar, Dileep; Iftikhar, Anum; Imtiaz, Mehwish; Ali, Naib (Pakistan Journal of Health Sciences, 2026)
Temporary intestinal stomas are to preserve the distal anastomosis following colorectal surgery. Although stoma reversal is necessary to provide bowel continuity, the time of closure is debatable. Early closure might be more beneficial by minimizing stoma complications, hospitalization, and adverse psychosocial effects. Objectives: To compare clinical outcomes and psychosocial effects of early versus delayed stoma closure in patients with temporary stomas. Methods: This retrospective cohort study was done in the Surgical Wards of Jinnah Postgraduate Medical Centre (JPMC), Karachi, and involved 81 patients whose intestinal stoma was reversed. Patients were sorted into two groups: early closure (less than 6 weeks; n=40) and delayed closure (more than 6 weeks; n=41). The analysis of data was performed with the help of SPSS version 26. The p-value of 0.05 was taken to be statistically significant. Results: A total of 81 patients were included, with 40 undergoing early and 41 delayed stoma closure. Baseline characteristics were comparable between groups. Early closure was associated with shorter hospital stay (4.3 ± 1.9 vs 7.1 ± 2.4 days) and earlier resumption of oral intake (2.8 ± 1.2 vs 4.9 ± 1.8 days). Overall, postoperative complications were lower after early closure (17.5% vs 36.5%), particularly wound infection (10.0% vs 22.0%). Delayed closure showed higher psychological stress and greater socioeconomic burden. Conclusions: An earlier stoma closure had better clinical and psychosocial outcomes than a late stoma closure, which were characterized by quicker recovery.